The role of perfectionism in shaping the features of perception of time perspective and the image body in girls with anorexia nervosa - Y. V. Popov; A. A. Pichikov; P. A. Skripchenko; A. V. Trusova; E. Y. Tjavokina; A. S. Vasyk; Y. A. Puhovec (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The study has investigated the severity of different types of perfectionism in patients with anorexia nervosa compared with the normal population. Analyzed manifestations of perfectionism and related aspects of the behavior of girls with anorexia nervosa. Studied the degree of fixation on the negative events of the past and the difficulties with the perception of their future from them.